Assessing the moderating effect of institutional quality on economic growth: Carbon emission nexus in Nigeria - Anne C. Maduka; Stephen O. Ogwu; Chukwunonso S. Ekesiobi (African Governance and Development Institute (AGDI), 2022)
This study explores the relationship between economic growth and carbon dioxide and the moderating effect of institutional quality in Nigeria from 1990 to 2020, by employing long run and short run dynamic ARDL regression, quartile regression and granger causality test for the estimation. Utilizing CO2 per capita emissions, GDP per capita- a proxy for economic growth, capital stock (CAPSTK) - proxy for capital investment in Nigeria and Control of Corruption and Regulatory Quality (COC and RGQ) which represent the effective environmental regulations and laws put in place for the control and prevention of environmental degradation, the study found a significant cointegration between CO2 emissions and economic growth (lnGDP) in Nigeria. Furthermore, an N-shaped nexus exist between CO2 emissions and economic growth in the long run and short run instead of the inverted U-shape curve postulated by the EKC hypothesis. This was confirmed by both ARDL and quartile regression results. Similarly, InCAPSTK contributed significantly to the growth of CO2 emissions in Nigeria both in the long run and short run, although, the short run did so at 10% significant level. Contrary to expectations, control of corruption (COC), contributes significantly to CO2 emissions in the long run but when it interacts with income (InGDPCOC), it significantly contributes to the reduction of CO2 emissions. More so, Regulatory quality (RGQ) had no significant impact on CO2 emissions in Nigeria either in the long run or short run, even when it interacts with InGDP. This finding is further supported by the quartile regression outcomes and granger causality. The study therefore concludes that CO2 emissions - economic growth nexus in Nigeria assumes an N-shape both in the long run and short run. Based on the results, the study recommends that Government should pursue industrialization policy with sophisticated method of production that will bring about rapid economic progress and at the same time support environmental sustainability.
Keywords: O44; Q5; C5; 330; Regulatory Quality; Control of Corruption; Carbon Emission; Economic Growth; Quartile Regression; Environmental Sustainability